Analisis Karakter Prabu Dasamuka Melalui Nilai-Nilai Pendidikan Akhlak Islami - Nurngaini, Imam; Shofwan, Arif Muzayin (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
Prabu Dasamuka is a puppet character who has ten faces, a symbol of a cunning person and twenty hands, a symbol of an arrogant person. Some of the other characters are cruel, fierce, cruel, greedy, angry, and sorcerers. This qualitative research using literature studies analyzes the character of King Dasamuka through the values ​​of Islamic moral education. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research resulted in the conclusion that several of Prabu Dasamuka's characters should be avoided because they do not reflect the values ​​of Islamic moral education, including: ruthless, fierce and cruel, significant to the content of the QS. As-Shura verse 42, QS. Ibrahim verse 42, QS. Ash-Syu'ara verse 227, HR. Bukhari, Muslim, Turmudzi, Ahmad, Abu Daud, Hakim, Tabrani, and Nasai; significant greed with the content of QS. An-Nisa verse 37 which can cause stinginess and QS. Luqman verse 12 which can cause not being good at being grateful; arrogance, arrogance and high-mindedness are significant to the content of QS. Luqman verse 18, QS. Al-Isra verse 37, QS. Ghafir verse 56, QS. Al-A'raf verse 146, QS. Al-Mukmin verse 35, QS. Al-Baqarah verse 34, HR. Bukhari and Muslim; Angkara is significantly angry with the contents of the QS. Yusuf verse 53 about lust and anger, HR. Bukhari, and HR. Turmudzi; significant magical acts with the contents of the QS. Al-Baqarah verse 102, HR. Bukhari and Muslim, HR. Abu Daud and Ibn Majah.